PENGARUH PENGAWASAN TERHADAP KINERJA PEGAWAI DISPERINDAG SUB BIDANG PENGAWASAN BARANG DAN JASA PROVINSI RIAU - nielwaty, elly; prihati, prihati; zuhdi, sulaiman (Jurnal Niara, 2017)
This study aims to determine and analyze the influence of supervision on the performance of employees of industry and trade sub division of supervision of goods and services Riau Province and its inhibiting factors. The type of research used is survey research,primary data source is all employees of Industry and Trade Sub Division of Supervision of goods and services Riau Province amounting to 85 people.Sampling technique by probability with census / saturated sampling technique is the sample taken based on the total population.Data analysis is done descriptively quantitative.The result of the research shows that supervision has positive and significant effect on employee performance with coefficient of determination (r2) value is 0,932,Meaning that 93.2% of employee performance is influenced by supervision.The inhibiting factor in supervision is that the leadership has not conducted regular and structured supervision.In addition there are difficulties in the supervision of goods and services in circulation because many new products and not in accordance with the standards.